Community Perceptions About National Health Insurance To Participation To Be A BPJS Health - Totok Sundoro (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: The Government of the State of Indonesia requires all its citizens to participate as BPJS Health participants so that all Indonesians receive health insurance to meet the basic needs of a decent life and increase the degree of dignity in their lives. A person's perception is a stimulus that influences a person to act or respond (acceptance) directly from something, or it also means the process of someone knowing some things through his five senses. Purpose: This study was conducted to determine whether there is a relationship between public perception of the National Health Insurance (JKN) and participation in BPJS Kesehatan in Wonolelo Pleret Village, Bantul. Method: This research is quantitative with a cross-sectional study design. The sample in this study was 100 samples which were BPJS Health participants. The results showed that there was a relationship between public knowledge (p = 0.000), community needs (p = 0.000), community expectations (p = 0.004) and the environment (p = 0.001) with their participation as BPJS Health participants. Meanwhile, there is no relationship between product appearance (p=0.161) and involvement in BPJS Health. Conclusion: This study concludes that there is a relationship between community knowledge, community needs, community expectations and the community environment with their participation in BPJS Health